GF floor tiles layout and finishes plan ( RFA-493_Rev B) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF & DWG version of drawings.